(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text identifies and analyzes the main framings produced by the Portuguese newspaper Público, regarding the protest held by the transgender activist Keyla Brasil during the presentation of the play All about my mother at the São Luiz Theater in Lisbon. The article concludes that the news pieces with more negative bias towards the act, transgender violence, the inviolability of artistic creation, and the idea that theater is the art of representation stood out in the overall reading of the published material. Conversely, more favorable texts accentuate a portrayal of the violence inherent in the conditions faced by trans migrants. They achieve this by juxtaposing the violence depicted on stage with the harsh reality of trans existence.